Obesity — A Risk Factor for Psoriasis and COVID-19() - Llamas-Velasco, M. (Actas Dermosifiliogr, 2021)
Obesity is a major health problem whose well-known association with psoriasis has been amply described. The importance of obesity as a risk factor for poor prognosis in the coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 infection has recently been demonstrated. This review examines a possible relationship between obesity, psoriasis, and COVID-19, analyzing the pathophysiological links and their practical implications. On the one hand, a higher body mass index increases the risk of psoriasis and is also a factor in metabolic syndrome, which is common in patients with psoriasis and has been implicated in reducing the effectiveness of psoriasis treatments. On the other hand, obesity is a risk factor for severe COVID-19 and mortality. Obesity also promotes a proinflammatory state in the lung, where it compromises respiratory mechanics.